Impact of a rotating cone on forced convection of Ag-MgO/water hybrid nanofluid in a 3D multiple vented T-shaped cavity considering magnetic field effects - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Springer, 2021)
Forced convection of hybrid Ag-MgO/water nanofluid in a three-dimensional T-shaped vented cavity with multiple ports under the effects of a inner rotating cone and magnetic field is numerically studied with finite volume method. The simulation is performed for various values of parameters such as: Reynolds number (between 100 and 1000), Hartmann number (between 0 and 60), angular velocity of the rotating cone (between - 200 rad/s and 0), aspect ratio of the circular cylinders of the base of the cone (between 0.5 and 2) and nanoparticle solid volume fraction of the hybrid nanofluid (phi between 0 and 0.01, phi 2 between 0 and 0.01). It was observed that the average heat transfer rate rises with higher values of Reynolds number, Hartmann number above a specified value, angular rotational speed of the cone, aspect ratio of the cone for values above 1 and solid nanoparticle volume fractions of the hybrid particles. In total, 61% of average heat transfer enhancement for left horizontal upper surface is achieved with the imposed magnetic field. The enhancement in the average Nusselt numbers is 25.6% for the rotating cone at the highest angular velocity as compared to a motionless one. The average heat transfer increases almost linearly with hybrid solid nanoparticle volume fraction, while 8.96% and 15.52% enhancements are obtained for varying the solid volume fraction of the particles with the lower and higher thermal conductivity up to 0.01.
Keywords: 3D vented cavity; Hybrid nanofluid; Magnetic field effects; Finite volume method; T-shaped cavity